Notational analysis of shooting play in the middle area by world-class players and Japanese elite players in women's handball - Yamada, E.; Aida, H.; Nakagawa, A. (International Journal of Sport & Health Science, 2011)
In this study, we elucidated the shooting plays of women handball players in the middle area by comparing notational analysis of world-class players with that of Japanese elite players. Recent world-class players Anita Görbicz, Ludmila Postnova, and Mariama Signate were selected for comparison with 3 Japanese elite players. Results revealed the following: (a) Shooting plays by the world-class players were classified into three types consisting of various choices before shooting, various choices when shooting, and no choices when shooting, and (b) the Japanese elite players had a tendency to run toward their dominant arm and use an additional step when running following possession of the ball. They also combined the phases of the back swing and the forward swing.